2005
DOI: 10.1172/jci21386
|View full text |Cite
|
Sign up to set email alerts
|

Induction of dermal-epidermal separation in mice by passive transfer of antibodies specific to type VII collagen

Abstract: Epidermolysis bullosa acquisita (EBA) is a subepidermal blistering disorder associated with tissue-bound and circulating autoantibodies specific to type VII collagen, a major constituent of the dermal-epidermal junction. Previous attempts to transfer the disease by injection of patient autoantibodies into mice have been unsuccessful. To study the pathogenic relevance of antibodies specific to type VII collagen in vivo, we generated and characterized rabbit antibodies specific to a murine form of this antigen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
184
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 115 publications
(188 citation statements)
references
References 44 publications
4
184
0
Order By: Relevance
“…The current general immunosuppressive treatment consisting of dapsone and corticosteroids causes several undesirable side effects systemically [7,8], and a more specific therapy is required. Since autoantibodies targeting skin proteins have been shown to be pathogenic in several mouse models [24][25][26][27][28][29][30][31][32], it is appealing to interfere with their binding or function. Removing autoantibody-immune complexes by immunoadsorption or immunoapheresis is consequently an attractive strategy [33,34], but this is an intensive treatment, since the patient's plasma needs to be filtered multiple times.…”
Section: Discussionmentioning
confidence: 99%
“…The current general immunosuppressive treatment consisting of dapsone and corticosteroids causes several undesirable side effects systemically [7,8], and a more specific therapy is required. Since autoantibodies targeting skin proteins have been shown to be pathogenic in several mouse models [24][25][26][27][28][29][30][31][32], it is appealing to interfere with their binding or function. Removing autoantibody-immune complexes by immunoadsorption or immunoapheresis is consequently an attractive strategy [33,34], but this is an intensive treatment, since the patient's plasma needs to be filtered multiple times.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, repetitive injection of affinity-purified rabbit antibodies to murine COL7 into wild-type C57BL/6 mice, over a period of 12 days, results in a blistering phenotype closely mimicking inflammatory EBA. 19 To address the effect of IdeS treatment on blister formation in experimental EBA, we treated mice (n=4/group) with IdeS or PBS and, subsequently, injected them with rabbit IgG against murine COL7. Control mice developed initial blisters 4 days after the first injection of rabbit IgG to COL7, while widespread disease was observed 6 days after the first injection.…”
Section: Mice Treated With Ides Do Not Develop Skin Blistering Uponmentioning
confidence: 99%
“…Total IgG from immunized rabbits (with murine COL7c) and normal rabbit sera was purified by affinity chromatography using protein G affinity as previously reported. 19 Next, murine COL7c-specific IgG was isolated from purified total IgG using Affi-Gel (Bio-Rad, Munich, Germany). For IgG was filter-sterilized (pore size, 0.22 μm; Sartorius), and protein concentration was adjusted to 2.0 mg/mL.…”
Section: Affinity Purification Of Rabbit Antibodies Specific To Murmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31] Passive transfer mouse models using nude, BALB/c, C57BL/6 and SKH-1 mice have been developed by injecting mice with sera from immunized rabbits against murine or human recombinant NC1, which furthered the understanding of the pathogenic sequence of EBA in vivo. 32,33 Passively transferring the entire IgG fractions from human EBA patients induced blister formation in mouse skin. 34 These models showed that the neonatal Fc-receptor (FcRn), complement, activated neutrophils and reactive oxygen species (ROS) induce blister formation in EBA.…”
Section: Pathogenesismentioning
confidence: 99%